A devoção a Nossa Senhora em pacientes oncológicos - Vasconcelos, Michele Mileib de (2008)
This work has the aim to understand the meaning of the devotion to Our Lady in oncologic patients. When they come across the diagnosis of cancer, usually realized as a death sentence, the patient search to understand the sense of being ill, of dying and of life itself. This search for the sense, the spirituality, is not caused by the disease, but it can be revealed by it. Among the countless possible results of the search for the sense, the religion receives distinction here. The way each one stands before the beliefs, based as much on the culture that they are inserted as on individual questions, promotes individual experience inside the same religious perspective. Among the beliefs given by oncologic patients, I chose to treat here the devotion to Our Lady. Brazil is a country of catholic majority, in which the devotion to Maria is very much spread. From a case study, it was looked to point the possible senses of the devotion to Our Lady. There was concluded that Maria represents for the loyal ones a figure of intercession between God and the men and, mostly, a model of surrender and full confidence. At moments of great difficulty before the disease and treatment, Maria is seen as a mother, figure of support and acceptance, she re-understands her son s pains, she accompanies them and she appeals for them to do in accordance to the Divine Will